Representasi Sosial Budaya dan Kesenjangan Gender Pada Tari Lengger, Tari Bedhaya dan Tari Reog - Amira Juliani Surbakti; Dinda Melati Putri; Lidia Lestari; Mia Audia; Widy Kurniawan; Syairal Fahmy Dalimunthe (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
Dance serves as a significant reflection of human cultural heritage, and its role in shaping and reflecting socio-cultural realities remains debated. In this context, the concept of gender holds significant influence in shaping representations and social disparities within dance. This research aims to delve into the influence of gender concepts in dance, particularly within Javanese culture, focusing on contemporary dance practices. Through qualitative approaches and content analysis, the study reveals strong gender stereotypes and objectification of bodies in dance, as well as the idealization of women's roles in Javanese cultural guidelines. The findings highlight challenges to gender norms in traditional Javanese dance, while also indicating limitations in existing research, such as cultural context constraints and limited data. It is hoped that this research contributes to understanding the role of gender concepts in dance and their implications in society, while also providing a foundation for further research.